Improving Cocoa Drying Efficiency with a Mixed Forced Convection Solar Dryer in an Equatorial Climate - Arnaud Nzendjang Mbakouop; Claude Bertin Nzoundja Fapi; André Désire Siéwé; Hyacinthe Tchakounté; Awoh Innocentia Ankungha (Thermo)
A crucial stage in the post-harvest processing of cocoa beans, drying, has a direct effect on the finished product’s quality and market value. This study investigates the efficiency, quality outcomes, and environmental implications of a mixed forced convection solar dryer designed for drying cocoa beans in Ntui, Cameroon, compared to traditional open-air drying methods. The solar dryer’s design, incorporating a solar collector, forced ventilation, and thermal storage, leverages local materials and renewable energy, offering an environmentally sustainable alternative by reducing fossil fuel reliance and post-harvest losses. Experimental trials were conducted to assess key drying parameters, including the temperature, relative humidity, water removal rate, pH, and free fatty acid (FFA) content, under the equatorial climate conditions of high solar irradiation and humidity. Results demonstrate that the solar dryer significantly reduces drying time from an average of 4.83 days in open-air drying to 2.5 days, a 50% improvement, while maintaining optimal conditions for bean quality preservation. The solar-dried beans exhibited a stable pH (5.7–5.9), a low FFA content (0.282% oleic acid equivalent, well below the EU standard of 1.75%), and superior uniformity in texture and color, meeting international quality standards. In contrast, open-air drying showed greater variability in quality due to weather dependencies and contamination risks. The study highlights the dryer’s adaptability to equatorial climates and its potential to enhance cocoa yields and quality for small-scale producers. These findings underscore the viability of solar drying as a high-performance, eco-friendly solution, paving the way for its optimization and broader adoption in cocoa-producing regions. This research contributes to the growing body of knowledge on sustainable drying technologies, addressing both economic and environmental challenges in tropical agriculture.